2021
DOI: 10.48550/arxiv.2102.02432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The use of a time-fractional transport model for performing computational homogenisation of 2D heterogeneous media exhibiting memory effects

Libo Feng,
Ian Turner,
Patrick Perre
et al.

Abstract: In this work, a two-dimensional time-fractional subdiffusion model is developed to investigate the underlying transport phenomena evolving in a binary medium comprised of two sub-domains occupied by homogeneous material. We utilise an unstructured mesh control volume method to validate the model against a derived semi-analytical solution for a class of two-layered problems. This generalised transport model is then used to perform computational homogenisation on various two-dimensional heterogenous porous media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To date, Zeng et al [36] used a discrete least squares collocation method to deal with a coupled system of time-fractional diffusion equations with different fractional indices in an irregularly shaped region. Feng et al [21,37] proposed a two-dimensional time-fractional model to study the underlying transport phenomena in a binary medium based on the Riemann-Liouville fractional derivative, in which it showed that the generalised transport model could exhibit the correct physical solution behaviour and produce a more accurate overall mass balance. In this section, we focus on a two-layered problem with a tempered operator (see Fig.…”
Section: Application Iii: Tempered Two-layered Problemsmentioning
confidence: 99%
“…To date, Zeng et al [36] used a discrete least squares collocation method to deal with a coupled system of time-fractional diffusion equations with different fractional indices in an irregularly shaped region. Feng et al [21,37] proposed a two-dimensional time-fractional model to study the underlying transport phenomena in a binary medium based on the Riemann-Liouville fractional derivative, in which it showed that the generalised transport model could exhibit the correct physical solution behaviour and produce a more accurate overall mass balance. In this section, we focus on a two-layered problem with a tempered operator (see Fig.…”
Section: Application Iii: Tempered Two-layered Problemsmentioning
confidence: 99%
“…To date, Zeng et al [34] used a discrete least squares collocation method to deal with a coupled system of time-fractional diffusion with different fractional indices in an irregularly shaped region. Feng et al [19,35] proposed a 2D time-fractional model to study the underlying transport phenomena in a binary medium based on the Riemann-Liouville fractional derivative, in which it showed that the generalised transport model could exhibit the correct physical solution behaviour and produce a more accurate overall mass balance. In this section, we focus on a two-layered problem with a tempered operator (see Figure 7):…”
Section: Numerical Examplesmentioning
confidence: 99%